Kajian Timbulan, Komposisi dan Nilai Recovery Factor Sampah di TPS 3R Kampung Injeuman, Desa Cibodas - Nada Noer Halimah; Pramiati Purwaningrum; Lailatus Siami (Jurnal Serambi Engineering, 2022)
Waste management in Kampung Injeuman Cibodas Village, Pasirjambu District, Bandung Regency still applies the conventional concept (collect-transport-dispose). This management approach does not support the vision of Desa Cibodas towards Eco-Village. In order to realize the vision of Cibodas Village through waste management at TPS 3R Kampung Injeuman, it is necessary to study the generation, composition and value recovery factor at TPS 3R Kampung Injeuman. The method of measuring data directly at the research site includes the generation of waste entering the 3R TPS, waste density, and waste composition using the load count analysis method based on SNI 19-3964-1994. Waste generation at TPS 3R Kampung Injeuman is 1,015,445 kg/day consisting of organic waste of 704,755 kg/day and non-organic waste of 310,7 kg/day. Then, from the composition data, it is known that waste that can still be reused is represented in percent of the recovery factor for organic waste of 91,81%; plastic waste by 46,69%; paper waste by 80.942%; metal waste by 100%; glass waste by 70%; and cloth waste by 58,67%.